Monitoring of the Environment at the Transplant Unit—Hemato-Oncology Clinic - Matoušková, Ivanka (MDPI, 2014)
Aims: Aim of this study was to monitor the environment at the Transplant Unit—Hemato-Oncology Clinic, University Hospital Olomouc (Olomouc, Czech Republic) and identify risks for the patients. Methods and Results: Microorganisms were cultivated under standard aerobic conditions. Strains were biochemically identified using the BD Phoenix™ PID Panel (USA). Legionella pneumophila was identified by DNA sequencing. From the air, the most frequently isolated strains were coagulase-negative staphylococci (94.3%), Micrococcus spp. and Bacillus spp. No Gram-negative strains were isolated from the air. From the surfaces, the most frequently isolated Gram-positive strains were coagulase-negative staphylococci (67.4%), Bacillus spp., enterococci (5.5%), Staphylococcus aureus (2.3%) and Micrococcus spp. (1.7%). From the surfaces, the most frequently isolated Gram-negative strains were from genera Pseudomonas (28%), Enterobacter (28%), E. coli (6%), and Klebsiella spp. (5%). From the personnel, the most frequently isolated Gram-positive strains were coagulase-negative staphylococci (59.6%), Bacillus spp. (24.1%) and Staphylococcus aureus (9.8%). From the personnel, the most frequently isolated Gram-negative strains were Enterobacter spp. (61%), Klebsiella oxytoca (18%), and E. coli (11%). Microscopic filamentous fungi were isolated in 13 cases (2.71%). Isolated strains were Aspergillus spp. (4), Trichoderma spp. (2), Penicillium spp. (2), one case of the strains Paecilomyces spp., Eurotium spp., Monilia spp. Conclusions: The study found no significant deviations in the microbial contamination of the cleanroom air. The personnel entrance of the Transplant Unit represent a high risk area, an extreme value (7270 CFU/m(3)) was recorded. Regime measures are fully effective, no other deficiencies were found. Significance and Impact of the Study: This epidemiological study, which was held for the duration of one year at the Transplant Unit—Hemato-Oncology Clinic, University Hospital Olomouc. The study monitored microbial contamination of the cleanroom air, surfaces, water, colonization of the personnel by bacterial strains of epidemiological consequence.